Preliminary Pharmacological Screening of Momordica charantia Linn. Leaves Extracts for Antiulcer Effect on Albino Rats: Pharmaceutical Science-Pharma - Singh, Punit; Kori, Mohan Lal (International Journal of Life Science and Pharma Research, 2022)
Ulcer is defined as a rupture in the skin or mucus membrane with loss of surface tissue. It has defects in the epithelium, caused by a lesion with a lost epithelial layer in the stomach or diffused loss of mucosal layer within the oral cavity. The present study aimed to investigate the preliminary screening of Momordica charantia Linn. leaves for oral and stomach ulcers. The leaves of Momordica charantia Linn. were extracted with different solvents with increasing polarity. Preliminary phytochemical tests were carried out to detect the presence of various chemical constituents in petroleum ether, chloroform, ethyl acetate, ethanol, and aqueous extracts. Initial screening was done for the antiulcer effect on ethanol-induced stomach ulcers and glacial acetic acid oral ulcers. The antiulcer effect was observed by they measured the ulcer index, percentage inhibition of ulcer, gastric pH, total acidity, and gastric volume. In addition, biochemical assessments of proinflammatory mediators (TNF-α, IL-6, and PGE-2) were performed in mucosal tissues. Results of phytochemical screening revealed the presence of steroids, terpenoids, alkaloids, flavonoids, tannins, glycosides, and phenolic compounds. Results of in vivo study showed that the antiulcer effect was observed in a dose-dependent manner. Ethanolic extract of Momordica charantia Linn. with 200 and 400mg/kg b.w. Doses have significant antiulcer potential and were comparable to the standard (Omeprazole and ORASORE Gel). A significant (p<0.05) reduction in ulcer index and percent inhibition was observed in the stomach and oral cavity ulcers. Furthermore, the practical (p<0.05) restoration of inflammatory mediators indicated a supporting mechanism of ulcer healing of ethanolic extract. In conclusion, the antiulcer effect was shown in a dose-dependent manner may be due to the presence of secondary metabolites like phenolic compounds viz., flavonoids, and tannins in the ethanolic extract of Momordica charantia Linn.